Предмет: Алгебра,
автор: PlisetskyYuri
помогите пожалуйста.
Упростить: 6(p-q)(p+q)-6p^2+12q^2=
Решите уравнение:
1).(х-4)(х+4)-х^2=2х;
2).х+2-х(х+2)=0.
Ответы
Автор ответа:
2
Решение:
1)
6(p-q)(p+q)-6p^2+12q^2=6p²-6g²-6p²+12g²=6g²
2)
(х-4)(х+4)-х^2=2х
x²-16-x²-2x=0
-2x=16
x=16/(-2)
x=-8
Проверка:
(-8-4)(-8+4)-(-8)²=2×(-8)
-12×(-4)-64=-16
-16=-16
Ответ: x= -8
1)
6(p-q)(p+q)-6p^2+12q^2=6p²-6g²-6p²+12g²=6g²
2)
(х-4)(х+4)-х^2=2х
x²-16-x²-2x=0
-2x=16
x=16/(-2)
x=-8
Проверка:
(-8-4)(-8+4)-(-8)²=2×(-8)
-12×(-4)-64=-16
-16=-16
Ответ: x= -8
PlisetskyYuri:
Спасибо!!! А там ещё одно уравнение
Похожие вопросы
Предмет: Геометрия,
автор: z719334
Предмет: Физика,
автор: nastya10349064
Предмет: Физика,
автор: Аноним
Предмет: Математика,
автор: vikav123
Предмет: Литература,
автор: ekaterina20062